Beyond Recognition: The Promise of Biometric Analytics. - Ricanek, Karl (Computer (00189162), 2014)
In the near future, we might be able to use biometric analytics to help answer everyday questions such as: Is the speaker on TV being honest? How much money will I need for retirement? Will using this cosmetic really make me look younger?